2023
DOI: 10.3390/metabo13010101
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Role of Autophagy in the Pathogenesis and Development of NAFLD

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a spectrum of liver disease, ranging from simple steatosis to hepatitis, fibrosis, cirrhosis, and hepatocellular carcinoma (HCC). Liver fibrosis, which portends a poor prognosis in NAFLD, is characterized by the excessive accumulation of extracellular matrix (ECM) proteins resulting from abnormal wound repair response and metabolic disorders. Various metabolic factors play crucial roles in the progression of NAFLD, including abnormal lipid, bile acid, and endotoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 114 publications
2
3
0
Order By: Relevance
“…As the primary enzyme involved in cellular response to oxidative damage, SOD may be more sensitive to toxic substances than CAT and GSH. , Thus, due to the compensation mechanism of organisms, the initial perturbations of TBPH on CAT and GSH can be compensated at 0.1 μg/L, while those on SOD are not sufficient to be offset . These results confirmed that embryonic exposure to TBPH led to hepatic lipid metabolism disorders and oxidative stress, the most prominent features of NAFLD . Consistently, a previous study found that TBPH aggregated hepatic lipid metabolic disorders induced by diet and caused oxidative stress, leading to the promotion of NAFLD progression .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As the primary enzyme involved in cellular response to oxidative damage, SOD may be more sensitive to toxic substances than CAT and GSH. , Thus, due to the compensation mechanism of organisms, the initial perturbations of TBPH on CAT and GSH can be compensated at 0.1 μg/L, while those on SOD are not sufficient to be offset . These results confirmed that embryonic exposure to TBPH led to hepatic lipid metabolism disorders and oxidative stress, the most prominent features of NAFLD . Consistently, a previous study found that TBPH aggregated hepatic lipid metabolic disorders induced by diet and caused oxidative stress, leading to the promotion of NAFLD progression .…”
Section: Resultssupporting
confidence: 84%
“…62 These results confirmed that embryonic exposure to TBPH led to hepatic lipid metabolism disorders and oxidative stress, the most prominent features of NAFLD. 63 Consistently, a previous study found that TBPH aggregated hepatic lipid metabolic disorders induced by diet and caused oxidative stress, leading to the promotion of NAFLD progression. 16 In addition, the administration of DEHP, a homologue of TBPH, was shown to disrupt lipid metabolic homeostasis in mouse livers and induce hepatic inflammation, as seen in NAFLD.…”
Section: Confirming the Effects On Lipid Metabolism Andsupporting
confidence: 69%
“…Details of the study protocol and baseline demographic characteristics have been described. 29 , 30 To ensure good fixation, one eye from each recruited patient, that is, the eye with better acuity, was chosen for the study. All subjects underwent complete eye examination, multimodal imaging (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), a typical pathogen-associated molecular pattern, mediates inflammatory injury in hepatocytes and has been found to induce inflammatory liver injury through the downstream toll-like receptor 4 (TLR4) signaling pathway (Qi et al, 2020;An et al, 2022). LPS is a crucial factor in the induction of inflammatory responses in the liver and is expressed abundantly in patients with NASH (Carpino et al, 2020).…”
Section: Inhibiting Gut-derived Lps and Tlr4 Signalingmentioning
confidence: 99%